1999
DOI: 10.1161/01.atv.19.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cholesterol Transport and Efflux in Fibroblasts Are Abnormal in Subjects With Familial HDL Deficiency

Abstract: Abstract-Familial high density lipoprotein (HDL) deficiency (FHD) is a genetic lipoprotein disorder characterized by a severe decrease in the plasma HDL cholesterol (-C) level (less than the fifth percentile). Unlike Tangier disease, FHD is transmitted as an autosomal dominant trait. FHD subjects have none of the clinical manifestations of Tangier disease (lymphoid tissue infiltration with cholesteryl esters and/or neurological manifestations). Plasmas from FHD subjects contain pre-␤-migrating HDLs but are def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 62 publications
3
74
1
1
Order By: Relevance
“…HDL-mediated cholesterol efflux capacity has been demonstrated to be reduced in diabetes (46), in subjects with familial HDL deficiency (47), and in Tangier disease (48) and has been associated with an alteration in HDL concentration, distribution, or composition and structure. In vitro studies have shown that HDL-mediated cholesterol efflux is impaired by whole cigarette smoke extracts through lipid peroxidation (49).…”
Section: Discussionmentioning
confidence: 99%
“…HDL-mediated cholesterol efflux capacity has been demonstrated to be reduced in diabetes (46), in subjects with familial HDL deficiency (47), and in Tangier disease (48) and has been associated with an alteration in HDL concentration, distribution, or composition and structure. In vitro studies have shown that HDL-mediated cholesterol efflux is impaired by whole cigarette smoke extracts through lipid peroxidation (49).…”
Section: Discussionmentioning
confidence: 99%
“…The efflux of cholesterol from cells is mediated predominantly by ABCA1, which is a member of the ATP binding cassette transporter superfamily that contains 12 putative transmembrane domains and two ABCs (13,14). The importance of ABCA1 is shown by Tangier disease, in which ABCA1 deficiency results in the accumulation of cholesteryl esters in various tissues and clinically shows markedly enlarged yellow tonsils and very low HDL cholesterol levels (15)(16)(17)(18). ABCA1 promotes the transport of cholesterol and phospholipids across cell membranes, where these lipids then complex with acceptor particles, such as apolipoprotein A-I, leading to HDL formation (14), thereby reg-ulating cellular cholesterol homeostasis (19).…”
mentioning
confidence: 99%
“…Japanese-AmericanslivingintheUnitedStatesaregeneti-thesumoftheradioactivityinthemediaandcells 28) . Theabilityofindividualserumtopromotecholesterol efflux was calculated by subtracting values obtained withoutserum inorder toexclude theeffects of passivediffusion.Tominimizeintra-assayvariability,each serum sample was run in triplicate, and the average andstandarddeviationvalueswerecalculatedforeach percent of efflux obtained.…”
Section: Biochemical Analysesmentioning
confidence: 99%